Disputable provisions of the new Criminal Code of Kazakhstan Republic - A. K. Mindagulov (Russian Journal of Economics and Law, 2014)
Objective: to reveal, describe and explain the main disputable provisions of the new Criminal Code of Kazakhstan Republic, and to propose means for their solution. Methods: the methodological basis of the research is general cognition methods. Results: Critical evaluation is made of particular provisions of the Criminal Code of Kazakhstan Republic, which allows to define the main directions of its improving in a short-term period. Scientific novelty: For the first time in the Russian scientific literature the disputable provisions of the 2014 Criminal Code of Kazakhstan Republic are described and explained, which is useful for the Russian law-making activity. This constitutes the practical value of the research. Practical significance: The research is topical due to the fact that the issues of criminal-legal influence upon the criminality preserve their scientific and practical significance both for the Russian Federation and Kazakhstan Republic, while applying the foreign experience of legal regulation is one of the main directions of the modern Russian Criminal Law science.